DOMINANT TYPE OF SUNDANESE GRAMMATICAL INTERFERENCE IN ENGLISH SENTENCES AT NURUL WAFA ISLAMIC BOARDING SCHOOL - Asriani, Risa; Ardiansyah, Erlan Aditya; Nurholis, Nurholis (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This study discusses Sundanese grammatical interference from bilingual students at Nurul Wafa Islamic Boarding School. This school applies English as a second language used in daily activities. However, in the use of English language by students, many English sentences are influenced by their mother tongue, Sundanese. This is what then causes language interference, and mostly occurs in the grammatical aspect which includes structural and morphological elements. The purpose of this study is to determine the dominant type of grammatical interference in students’ english sentences at Nurul Wafa Islamic Boarding School. This research used descriptive qualitative method, and as for the data analysis, the researcher uses Weinreich's theory regarding the types of grammatical interference. The writer also made observations for data collection methods.As the result, the findings of this study indicated that there are two types of grammatical interference which are equally dominant in the 15 data analysis from the sentences that mixed with Sundaese particle (rarangkén and kecap pangateb) and from sentences that contain errors and interference in the use of Subject-Verb agreement, passive voice and  tenses; misplaced structures or word orders pattern, In the two types of sentences, each found 11 types of sentences analyzed. In conclusion, the types of "Transfer of morpheme" and "Application of grammatical elements" are both dominant in this study.Keywords:  Grammatical, Interference, Language, Sundanese